2021
DOI: 10.1155/2021/6662831
|View full text |Cite
|
Sign up to set email alerts
|

HGF-Modified Dental Pulp Stem Cells Mitigate the Inflammatory and Fibrotic Responses in Paraquat-Induced Acute Respiratory Distress Syndrome

Abstract: Paraquat (PQ) poisoning can cause acute lung injury and progress to pulmonary fibrosis and eventually death without effective therapy. Mesenchymal stem cells (MSCs) and hepatocyte growth factor (HGF) have been shown to partially reverse this damage. MSCs can be derived from bone marrow (BM-MSCs), adipose tissue (AD-MSCs), umbilical cord (UC-MSCs), dental pulp (DPSCs), and other sources. The biological characteristics of MSCs are specific to the tissue source. To develop an effective treatment for PQ poisoning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have been shown to contribute to tissue repair regeneration through secreting cytokines and extracellular vesicles [5][6][7][8]. However, the ability of MSCs to "home" to injured tissue is controversial, because most MSCs are actually trapped in pulmonary capillaries after intravenous administration [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have been shown to contribute to tissue repair regeneration through secreting cytokines and extracellular vesicles [5][6][7][8]. However, the ability of MSCs to "home" to injured tissue is controversial, because most MSCs are actually trapped in pulmonary capillaries after intravenous administration [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, human umbilical cord MSCs secrete EVs enriched with miR-377-3p, which can attenuate LPS-induced ALI by down-regulating mammalian target of rapamycin (mTOR) to inhibit the expression of inflammatory factors and induce autophagy, both in vivo and in vitro [ 127 ]. Another study found that DPSCs, particularly DPSCs modified to overexpress hepatocyte growth factor (HGF), had a stronger effect than umbilical cord MSCs to inhibit lung inflammation and fibrosis and improve the survival rate of a paraquat poisoning-induced ALI/ARDS mice model [ 128 ]. Similarly, MSC-EV treatment prevented AEC injury caused by mitochondrial gene damage in cigarette-exposed mice by transferring mitochondrial DNA with functional copies [ 129 ].…”
Section: Role Of Msc-evs In the Treatment Of Ali/ardsmentioning
confidence: 99%
“…Fibrosis is defined by the accumulation of excess ECM components, which can affect any organ and is responsible for up to 45% of all deaths in the industrialized world. 70 It has been reported that HGF/MSCs could reduce fibrosis efficiently in various diseased organs, including the heart, 68 , 71 lung, 29 , 55 , 72 , 73 , 74 liver, 47 , 52 , 56 , 75 , 76 , 77 , 78 kidney, 45 , 49 bladder, 79 bone 48 and skin. 62 Collagen (COL) is the most important component of ECM, hydroxyproline is the most important component of COL, and fibronectin (FN) is the most important non‐collagenous component of ECM.…”
Section: Promoting Anti‐fibrosis Effectmentioning
confidence: 99%